2014
DOI: 10.1111/1574-6941.12416
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput sequencing ecotoxicology study of freshwater bacterial communities and their responses to tebuconazole

Abstract: The pollution of lakes and rivers by pesticides is a growing problem worldwide. However, the impacts of these substances on microbial communities are still poorly understood, partly because next-generation sequencing (NGS) has rarely been used in an ecotoxicology context to study bacterial communities despite its interest for accessing rare taxa. Microcosm experiments were carried out to evaluate the effects of tebuconazole (TBZ) on the structure and composition of bacterial communities from two types of fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…More recently, the development of next-generation sequencing techniques and biological computational tools has allowed cost-effective, large-scale multiplexing analyses, which have transformed our understanding of the interactions between microbial communities and their niche [2][3][4][5][6]. This approach has opened a window onto the enormous taxonomic and functional diversity of the microbial community of the human body, called the microbiota [7].…”
Section: Proteobacteria In Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the development of next-generation sequencing techniques and biological computational tools has allowed cost-effective, large-scale multiplexing analyses, which have transformed our understanding of the interactions between microbial communities and their niche [2][3][4][5][6]. This approach has opened a window onto the enormous taxonomic and functional diversity of the microbial community of the human body, called the microbiota [7].…”
Section: Proteobacteria In Dysbiosismentioning
confidence: 99%
“…As the name suggests, members of the phylum Proteobacteria have greatly variable morphology and versatile physiology, which gives them a competitive edge in surviving in various ecological niches. Proteobacteria has been observed to be ubiquitous in habitats such as soil [2], plants [4], seawater [5], freshwater [3], the atmosphere [6], and mammalian body sites [7,48] ( Figure I). The phylum comprises six bacterial classes: Alpha-, Beta-, Gamma-, Delta-, Epsilon-, and Zetaproteobacteria.…”
Section: Host Nutrition and Metabolic Disordersmentioning
confidence: 99%
“…The fungicide also reduced species richness of aquatic hyphomycetes at all concentrations tested and modified the kinetics of β‐glucosidase, β‐xylosidase and cellobiohydrolase, resulting in slow cellulose degradation by leaf‐associated microorganisms (Artigas et al ., ). TBZ effects on aquatic ecosystems have been also studied in biofilm and plankton microbial communities (Artigas et al ., ; Pascault et al ., ), where different functional indicators showed variable responses to TBZ, whereas bacterial community structure was unaffected. Bacteria associated with decomposing leaves are also inhibited by TBZ, although less than fungi (Bundschuh et al ., ; Artigas et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased use of pesticides and novel nanoparticles puts increased stress on aquatic ecosystems, including bacterial biofilms. Pascault et al (2014) combined classical methods and next-generation sequencing to investigate the responses of microbial communities to the pesticide tebuconazole (TBZ). They revealed that bacterial diversity was higher in rivers than in lakes and in previously exposed sites than in pristine sites.…”
Section: Invertebrate-associated Benthic Bacteriamentioning
confidence: 99%